A Multimodal Semiotics Approach to The Discourse of Zenius Education Advertisement - Irianti, Yesi (Jurnal Riset Ilmu Pendidikan, 2024)
The use of semiotics and multimodal approaches in advertising has gained significant traction in recent years. Semiotic multimodality allows individuals to connect with five key systems: linguistic, visual, audio, gestural, and spatial. This study aims to describe the five semiotic modes regarding their purposes and the relationships between verbal and visual texts and messages present in advertisements. The analysis is based on the multimodal semiotic framework proposed by Michèle Anstey and Geoff Bull (2018), which emphasizes these five systems. For this research, three advertisements from Zenius Education's YouTube channel were examined: "Bikin Cerdas Beneran #MulaiDariManaAja," "Pahlawan masa depan - #ZeniusUntukSemua," and "Mentok Ngerjai Latihan Soal? Tanya Zenbot Aja! #CekrekLangsungNgerti." A descriptive qualitative research method, following Miles and Huberman's approach, was employed to gather data. This involved browsing, selecting, downloading, printing, and identifying elements to analyze the five multimodal semiotics within the advertisements. The findings indicated that Zenius Education effectively utilized multimodal semiotic systems, incorporating linguistic, visual, audio, gestural, and spatial elements. These five systems were integrated to convey meanings and messages within the Zenius advertisements, aiming to capture the attention of potential customers and encourage the use of their tutoring platform services